2019
DOI: 10.1039/c9se00074g
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pt metal loading on the atomic restructure and oxygen reduction reaction performance of Pt-cluster decorated Cu@Pd electrocatalysts

Abstract: Galvanic replacement dominates the structure of Pt decorated Cu@Pd nanoparticles. With proper Pt loading, it converts Cu@Pd-Pt from a surface disordered structure to multiple twin particles (MTPS) and gain the highest stability in the oxygen reduction reaction among the experimental samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…As shown in Figure 2a, the two absorption peaks "M" and "N" correspond to the electron transition from Pd 1s core-orbital to unoccupied 5p and 4f states, respectively, 36,37 while their intensity is directly related to the unoccupied density of Pd 5p/ 4f orbitals (i.e., the extent of electron transition between Pd and the neighboring atoms). 38 Additionally, the Pd species with higher surface oxygen chemisorption (O ads ) shows higher absorption peak intensities. Meanwhile, the position of the inflection point (I) mainly elucidates the oxidation state of the Pd atoms.…”
Section: ■ Experimental Sectionsupporting
confidence: 85%
See 1 more Smart Citation
“…As shown in Figure 2a, the two absorption peaks "M" and "N" correspond to the electron transition from Pd 1s core-orbital to unoccupied 5p and 4f states, respectively, 36,37 while their intensity is directly related to the unoccupied density of Pd 5p/ 4f orbitals (i.e., the extent of electron transition between Pd and the neighboring atoms). 38 Additionally, the Pd species with higher surface oxygen chemisorption (O ads ) shows higher absorption peak intensities. Meanwhile, the position of the inflection point (I) mainly elucidates the oxidation state of the Pd atoms.…”
Section: ■ Experimental Sectionsupporting
confidence: 85%
“…Figure a,b shows the normalized Pd K-edge X-ray absorption near-edge structure (XANES) and Fourier-transformed extended X-ray absorption fine structure (FT-EXAFS) spectra of CNP NCs, respectively, while the Pd-CNT was compared as the reference sample. As shown in Figure a, the two absorption peaks “M” and “N” correspond to the electron transition from Pd 1s core-orbital to unoccupied 5p and 4f states, respectively, , while their intensity is directly related to the unoccupied density of Pd 5p/4f orbitals (i.e., the extent of electron transition between Pd and the neighboring atoms) . Additionally, the Pd species with higher surface oxygen chemisorption (O ads ) shows higher absorption peak intensities.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, as the ORR activity is more facile at optimal metal loading on the substrates, [52][53][54] we first examined the effect of in-situ catalyst loading by using the Pd/NRGO samples with various Pd loading in the range of 22-47% (Fig. S6, 7).…”
Section: Evaluation Of Orr Performancesmentioning
confidence: 99%
“…Based on the aforementioned arguments and in line with recent developments, in the present study, we synthesized a ternary NC comprising hierarchical Ni@Pd NC with Pt-clusters decoration on the surface via a "self-aligned" heterogeneous nucleation-crystal growth mechanism on carbon black support (namely Ni@Pd-Pt). Our previous studies demonstrated that Pt-clusters decoration effectively shelters the catalyst surface from oxidation and creates intense active sites for HER facilitation [26][27][28][29][30][31]. In such a unique structure, Pt-clusters are decorated on the Ni@Pd surface and at the heteroatomic interfaces of Ni-to-Pd; where the ligand effect (due to difference in electronegativity of adjacent atoms) and lattice strain (due to lattice mismatch) plays a key role at the heterogenous interfaces and relocate electrons to the NC surface, hence, the formation of catalytic active sites takes place, which boosts the HER kinetics.…”
Section: Introductionmentioning
confidence: 99%